TRADITIONAL TECHNOLOGIES OF PRODUCTION OF SNACKS BASED ON CEREALS IN BENIN: IMPORTANCE OF NUTRITION, SOCIO-ECONOMIC CHARACTERISTICS AND TOXICOLOGICAL RISKS. - HOUANSOU, Gyraud; Guidi, Clotilde; AY, A; CHEGNIMONHAN, Kouamy Victorin; AGASSOUNON DJIKPO TCHIBOZO, Micheline (My University, 2018)
This literature review makes the point of the production technologies, socio-economic aspects, the nutritional importance and toxicological risk related to the cereal-based snack food. The sources of information used are the publications, books, reports of activities of theses and dissertations, and technical notes. It reveals the different technologies to produce snacks based on cereals. The production and sale of snacks are activities that provide cheaper products than in the restaurants. These activities are often exercised by women, who are mostly non-educated. Cereal, thanks to their nutritional, constitute an important food resource for Man. These foods provide the body with macronutrients (carbohydrates, proteins and fats) and micronutrients (iron, phosphorus, potassium, magnesium, calcium, and vitamins especially of the B group). However, these snacks may become sources of food poisoning for the consumer, because they may be contaminated with pathogenic microorganisms during their preparation or preservation. It is not uncommon that some fungal species of the genus Aspergillus, Fusarium and Penicillium, which produce mycotoxins and pose serious health risks to consumers even at low doses
Keywords: snacks; cereals; mycotoxins; health risk